2006
DOI: 10.1002/adsc.200600363
|View full text |Cite
|
Sign up to set email alerts
|

Formal Enantioselective [4+3] Cycloaddition by a Tandem Diels–Alder Reaction/Ring Expansion

Abstract: The tandem Diels-Alder reaction/ring expansion between cyclopentadiene and unsaturated aldehydes is a highly stereoselective process for the synthesis of bicycloA C H T U N G T R E N N U N G [3.2.1]octenones, the formal products of a [4 + 3] cycloaddition. When the initial cycloaddition was conducted in the presence of the chiral Lewis acid catalyst 14, the bicycloA C H T U N G T R E N N U N G [3.2.1]octenones were obtained in two steps in 72-85 % yields with up to 96 % ee and > 98 % de.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…The combination of Diels–Alder (DA) cycloaddition reactions with other transformations without isolating the intermediates allows a very rapid increase in the complexity of products. For example, Lewis acid promoted rearrangements of DA products have been reported recently. Davies and Dai showed that DA addition of alkylated acroleins with cyclopentadiene affords the formal [4 + 3] rather than the kinetic [4 + 2] cycloadducts under appropriate Lewis acid catalysis. , The reaction sequence comprises a domino DA and two consecutive 1,2-shifts, delivering bicyclo[3.2.1]­oct-6-en-3-ones 4 (Scheme , eq A). The rearrangement proved to be stereoselective with retained enantioselectivity introduced during the DA step . In contrast, α-oxy-substituted acroleins 5 and 9 were believed to undergo concerted [4 + 3] cycloadditions of allyl cations with both cyclic and acyclic dienes (Scheme , eqs B and C). …”
mentioning
confidence: 99%
“…The combination of Diels–Alder (DA) cycloaddition reactions with other transformations without isolating the intermediates allows a very rapid increase in the complexity of products. For example, Lewis acid promoted rearrangements of DA products have been reported recently. Davies and Dai showed that DA addition of alkylated acroleins with cyclopentadiene affords the formal [4 + 3] rather than the kinetic [4 + 2] cycloadducts under appropriate Lewis acid catalysis. , The reaction sequence comprises a domino DA and two consecutive 1,2-shifts, delivering bicyclo[3.2.1]­oct-6-en-3-ones 4 (Scheme , eq A). The rearrangement proved to be stereoselective with retained enantioselectivity introduced during the DA step . In contrast, α-oxy-substituted acroleins 5 and 9 were believed to undergo concerted [4 + 3] cycloadditions of allyl cations with both cyclic and acyclic dienes (Scheme , eqs B and C). …”
mentioning
confidence: 99%
“…Surprisingly, there have only been two reports of catalytic asymmetric (4+3) cycloadditions31 using nitrogen‐stabilized oxyallyl cations, but the potential for future development in this area is promising and merits further exploration.…”
Section: Catalytic Asymmetric (4+3) Cycloaddition Reactionsmentioning
confidence: 99%
“…Consequently, we turned our attention to chiral allenamide 31 -Bn, which was synthesized from enal 28 23 [ Scheme 5 ]. It was quickly evident that each of these internally tethered systems behaves quite differently.…”
mentioning
confidence: 99%